2001
DOI: 10.1089/109264201750539718
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Laparoscopy Decreases the Rate of Unnecessary Laparotomies and Reduces Hospital Costs in Trauma Patients

Abstract: Diagnostic laparoscopy might be used in selected patients to exclude significant intra-abdominal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 18 publications
1
52
0
6
Order By: Relevance
“…[1,4] Laparoscopy has recently been safely used for PAT patients for diagnostic and therapeutic purposes, avoiding unnecessary laparotomies, shortening the length of hospital stay, and reducing medical costs. [5,6] The aim of our study was to examine the use of diagnostic laparoscopy (DL) in the management of hemodynamically stable trauma patients with penetrating anterior abdominal injuries.…”
Section: Sonuçmentioning
confidence: 99%
“…[1,4] Laparoscopy has recently been safely used for PAT patients for diagnostic and therapeutic purposes, avoiding unnecessary laparotomies, shortening the length of hospital stay, and reducing medical costs. [5,6] The aim of our study was to examine the use of diagnostic laparoscopy (DL) in the management of hemodynamically stable trauma patients with penetrating anterior abdominal injuries.…”
Section: Sonuçmentioning
confidence: 99%
“…Penetrating trauma -stable patient The positioning and preparation of the patient for trauma laparoscopy is essentially the same as for a trauma laparotomy. Conversion to conventional open approach to the thorax and abdomen should be possible without delay or additional preparation as for every trauma laparotomy (5) .…”
Section: (3(mentioning
confidence: 99%
“…29 Laparoscopy-associated complications and morbidity are significantly lower than in cases of traditional laparotomy. [2][3][4] Recent research on the complications associated with diagnostic laparoscopy versus negative laparotomy showed reduced complication rates (3% versus 22%) and decreased hospital stay (1.4 versus 5.1 days). 2 Other studies have found that laparoscopies can significantly reduce hospitalisation-and complicationrelated costs when compared to the traditional laparotomy, with an estimated total reduction of 1.78-2 times.…”
Section: Benefits Of Laparoscopymentioning
confidence: 99%
“…2 Other studies have found that laparoscopies can significantly reduce hospitalisation-and complicationrelated costs when compared to the traditional laparotomy, with an estimated total reduction of 1.78-2 times. 3,4 Kaban et al reported that the laparoscopy had sensitivity and specificity rates of 92% and 100%, respectively, in detecting injuries. 30 Another study confirmed the superiority of laparoscopy over diagnostic peritoneal lavage with regards to sensitivity and specificity; additionally, no significant bleeding or trauma was observed during a subsequent laparotomy for 8% of those in the laparoscopy group compared to 27% of those in the peritoneal lavage group.…”
Section: Benefits Of Laparoscopymentioning
confidence: 99%
See 1 more Smart Citation